Comparative stress analysis of round shaft with shoulder fillet using finite element and analytical method. (2022) - Singh, Aditya Pratap; Vidya, Shrikant; Suresh, P.; Kumar, Amresh; Srikanth, K.S.
Abstract: In the design of machine elements asymmetry and sudden changes in dimensions of surface are unpreventable due to some characteristics of the element such as oil cavity and grooves, splines and keyways, shoulders and screw threads. But such discontinuities often lead to stress concentration near the irregularity due to which the stress near the irregularity is higher than the average stress in the whole member. In this study, rounded shaft with shoulder fillet is analyzed by theoretical method and finite element analysis. The round shaft is subjected to tensile loading and the stress concentration factor for different values of fillet radius is calculated. Further, the maximum stress is calculated theoretically and is compared with maximum stress computed by using Solid works. The static study shows that the level of error among analytical and fillet component arrangements has been viewed as <5%. And the error percentage decreases as the value of fillet radius increases.